Social trauma and the theatre: a study of the formation of a non-conformist identity - Vitalija Truskauskaite (Studia Ecologiae et Bioethicae)
The present article aims to analyze the social trauma implicit in the representation of the nonconformist identity formation in Judita Vaiciunaite’s play The Siege (Lithuanian Apsiaustis) directed by Giedrius Mackevicius. The play reflects on the experiences and inner states of characters as they struggle to survive in a seized city, wherein the motif of the seized city alludes to the political situation of Kaunas as a city seized by the totalitarian system. The play was performed by an amateur group in 1971 in the Kaunas Trade Unions Palace of Culture. The study relies on trauma studies by Danute Gailiene for the analysis of Giedrius Mackevicius’ debut experience; also it refers to the semantics of Judita Vaiciunaite’s play The Siege. In the staging of The Siege in 1971, on the contrary, the universal thematic dimension of this drama was emphasized.